Co-Innovating for more sustainable, climate responsive rice production in Chile - Witkowski, Kelly (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Over 200 people involved in the rice value chain participated in field days to observe research efforts and discuss the challenges and potential solutions to economically viable and more sustainable production. INIA has been working on genetic improvement and to validate and adapt the System of Rice Intensification (SRI), an agroecological method of producing rice that can reduce competition among plants, improve soil management, and change water management, leading to economic, agronomic, and environmental benefits. SRI has also been found to reduce methane emissions from rice cultivation. Participatory innovation groups bring farmers together to observe practices and evaluate crop development, while INIA's experimental station in San Carlos is testing surface and sub-surface drip irrigation to reduce water usage even further.